PENGARUH PENEMPATAN KARYAWAN DAN KESEHATAN KESELAMATAN KERJA TERHADAP SIKAP KARYAWAN DI PT. ANGKASA PURA 1 SIDOARJO - EMMYWATI EMMYWATI; IKA WIDYAWATI (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
Improper placement of employees with an interest will affect the company's performance. Therefore, a person will actually tend to feel tortured in their duties. This will not happen if the section manager of the Human Resources (HR) can make an assessment on the potential and interests of employees since the start of the recruitment process, if the employee in conditions not comfortable with the job while having more potential in other areas, which is precisely the company harmed. A study proves that excellent performance is only arise if there is a match between the characteristics, interests and skills of the individual with the company. In addition, as well as career or field of study. Research used quantitative approach . The result calculations, shows that there is a partial significant influence between independent variable (X1) on the dependent variable (Y), there is a positive and significant impact partially between the independent variables (X2) on the dependent variable (Y), there is a positive and significant influence simultaneously between the placement of employees (X1) and Health and Safety (X2) on employee attitudes (Y). Variable attitude of the employees affected by the variable placement of employees (X1), Health and Safety (X2), by 65% ​​while the remaining 35% is influenced by other variables.